Endoscopic lung volume reduction coil treatment in patients with very low FEV1: an observational study. (22nd February 2018) - Simon, Marcel; Harbaum, Lars; Oqueka, Tim; Kluge, Stefan; Klose, Hans
Background: Endoscopic lung volume reduction coil (LVRC) treatment is a therapeutic option for selected patients with advanced emphysema. The effects and the safety of endoscopic lung volume reduction in patients with very low forced expired volume in one second (FEV1 ) remain to be determined. This study was conducted to assess the effects and the safety of LVRC treatment in patients with very low FEV1 . Methods: The study was performed as a retrospective observational study in the Department of Respiratory Medicine at the University Medical Center Hamburg-Eppendorf on patients with very low FEV1, defined as an FEV1 ⩽ 20% of predicted at baseline in whom LVRC treatment was performed between 1 April 2012 and 28 February 2017. Results: LVRC treatment was performed in 33 patients with very low FEV1 . Of these, 45.5% were female and 54.5% were male. At baseline, mean FEV1 was 0.46 ± 0.12 liters (15 ± 3% of predicted), mean forced vital capacity (FVC) was 1.61 ± 0.62 liters (42 ± 13% of predicted), mean residual volume (RV) was 6.03 ± 0.81 liters (275 ± 51% of predicted) and 6-minute walk distance was 229 ± 102 m. Bilateral LVRC treatment was completed in 21 of these patients (63.6%). Bilateral LVRC treatment led to significant improvements in functional parameters with an increase in mean FEV1 from 0.44 ± 0.11 liters to 0.54 ± 0.12 liters ( p = 0.001), equivalent to a relative improvement of 24.5 ± 26.9%, an increase in mean FVC from 1.49 ± 0.54 liters to 1.84 ± 0.49 liters ( p = 0.001), a decrease in mean RV from 6.27 ± 0.83 liters to 5.83 ± 1.09 liters ( p = 0.004) and an improvement in 6-minute walk distance from 218 ± 91 m to 266 ± 96 m ( p = 0.01). There were no cases of respiratory failure requiring mechanical ventilation and no deaths. Conclusions: LVRC treatment was effective and safe in patients with very low FEV1 .